2019
DOI: 10.1002/aic.16617
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of mass transfer from particles by local shear‐rate and correlations with application to drug dissolution

Abstract: We analyze hydrodynamic enhancement of mass (or heat) release rate from small spherical particles within fluid flows from local flow shear-rate, with application to drug dissolution. Combining asymptotic theories in the high/low shear Peclet number limits in Stokes flow with 205 carefully-developed computational experiments, we develop accurate correlations for shear enhancement of Sherwood/Nusselt number (Sh/Nu) as a function of shear Peclet and Reynolds number (S * , Re S ). The data spanned S * from 0 to 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 17 publications
2
27
0
Order By: Relevance
“…These quantities represent the relative flow strength over the pill and the local diffusive mass flux, respectively. We have found that if there is substantial relative flow motion over the pill surface, the wall shear rate and the mass flux are indeed correlated not only globally as shown in the previous studies ( Abrahamsson et al, 2005 ; Bai and Armenante, 2009 ; Wang and Brasseur, 2019 ), but also locally as shown in the present study. It is observed, however, that if there is little relative motion between the pill and the flow, like the neutrally buoyant pill, the mass flux (concentration gradient) is almost independent of the wall shear rate.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These quantities represent the relative flow strength over the pill and the local diffusive mass flux, respectively. We have found that if there is substantial relative flow motion over the pill surface, the wall shear rate and the mass flux are indeed correlated not only globally as shown in the previous studies ( Abrahamsson et al, 2005 ; Bai and Armenante, 2009 ; Wang and Brasseur, 2019 ), but also locally as shown in the present study. It is observed, however, that if there is little relative motion between the pill and the flow, like the neutrally buoyant pill, the mass flux (concentration gradient) is almost independent of the wall shear rate.…”
Section: Discussionsupporting
confidence: 89%
“…This suggest that the positive correlation between the wall shear rate and the mass flux may only be valid for the pills heavier than the medium. This may be an important finding because many dissolution models have been derived from the correlation between the mass flux and the wall shear stress or wall shear rate ( Abrahamsson et al, 2005 ; Bai and Armenante, 2009 ; Wang and Brasseur, 2019 ).…”
Section: Discussionmentioning
confidence: 96%
“…Here, the obtained value of D m is close to 6:75 Â 10 À10 m 2 =s, which is expectedly small. The flow around the capsule induced by stirring is expected to enhance the release rate due to convection, 25,33,34 but not to significantly increase the intrinsic permeability of the capsule membrane.…”
Section: Application To Experimental Data Of Glucose Releasementioning
confidence: 99%
“…They have proposed Sherwood number correlations as a function of the blockage ratio. Recently, Wang and Brasseur [8] studied numerically mass transfer from a freely rotating sphere in shear flow and have proposed correlations valid over a wide range of the Péclet number. All these studies, and others summarized in Ref.…”
Section: Problem Statementmentioning
confidence: 99%